The Effects of a Roommate-Pairing Program on International Student Satisfaction and Academic Success - Tolman, Steven (Journal of International Students, 2017)
While great attention has been given to the growth of international students at U.S. institutions, there is a gap in the literature examining support for this student population within residence halls. To address the gap, this quantitative study evaluated an international roommate-pairing program (IRP) by comparing the residential experience of IRP participants with a control group. The results showed the roommate-pairing program had a positive impact on the residential experience of international students. These findings suggest physical environment and structured support are critical factors in the satisfaction and success of international students. This research can inform the practice of Residence Life professionals and aid in the establishment of effective support programs.